Substrate Rigidity Controls Activation and Durotaxis in Pancreatic Stellate Cells - Lachowski, Dariusz; Cortes, Ernesto; Pink, Daniel; Chronopoulos, Antonios; Karim, Saadia A.; P. Morton, Jennifer; del Río Hernández, Armando E. (Scientific reports, 2017)
Pancreatic Ductal Adenocarcinoma (PDAC) is an aggressive malignancy characterised by the presence of extensive desmoplasia, thought to be responsible for the poor response of patients to systemic therapies. Pancreatic stellate cells (PSCs) are key mediators in the production of this fibrotic stroma, upon activation transitioning to a myofibroblast-like, high matrix secreting phenotype. Given their importance in disease progression, characterisation of PSC activation has been extensive, however one aspect that has been overlooked is the mechano-sensing properties of the cell. Here, through the use of a physiomimetic system that recapitulates the mechanical microenvironment found within healthy and fibrotic pancreas, we demonstrate that matrix stiffness regulates activation and mechanotaxis in PSCs. We show the ability of PSCs to undergo phenotypic transition solely as a result of changes in extracellular matrix stiffness, whilst observing the ability of PSCs to durotactically respond to stiffness variations within their local environment. Our findings implicate the mechanical microenvironment as a potent contributor to PDAC progression and survival via induction of PSC activation and fibrosis, suggesting that direct mechanical reprogramming of PSCs may be a viable alternative in the treatment of this lethal disease.